2003
DOI: 10.1099/vir.0.19014-0
|View full text |Cite
|
Sign up to set email alerts
|

The latency protein LANA2 from Kaposi's sarcoma-associated herpesvirus inhibits apoptosis induced by dsRNA-activated protein kinase but not RNase L activation

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) uses several strategies to counteract the interferon (IFN) system. In this study, the relationship of the protein LANA2 from KSHV to the IFN-activated protein kinase (PKR) and 2-5A system was analysed. It was found that LANA2 could not abrogate apoptosis or RNA degradation mediated by the 2-5A system. However, expression of LANA2 inhibited apoptosis triggered by PKR. LANA2 also counteracted the PKR-mediated inhibition of protein synthesis and partially blocked PKR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 51 publications
(55 reference statements)
2
48
0
Order By: Relevance
“…No interaction has been observed between LANA2 and PKR. LANA2 inhibits PKR-induced activation of caspase 3 but not of caspase 9, suggesting that the FADD/ caspase 8 pathway is affected by LANA2 inhibition of PKRinduced apoptosis (93).…”
Section: Herpesviruses (I) Hsv-1mentioning
confidence: 99%
“…No interaction has been observed between LANA2 and PKR. LANA2 inhibits PKR-induced activation of caspase 3 but not of caspase 9, suggesting that the FADD/ caspase 8 pathway is affected by LANA2 inhibition of PKRinduced apoptosis (93).…”
Section: Herpesviruses (I) Hsv-1mentioning
confidence: 99%
“…102,103 Other viral proteins shown to inhibit PKR-mediated apoptosis include Kaposi's sarcoma-associated herpesvirus (KSHV)-encoded LANA2, as well as Epstein-Barr virus (EBV)-encoded RNAs (EBERs), which may inhibit PKR by preventing correct activation. [104][105][106] Influenza virus protein NS1 has been similarly reported to inhibit PKR, as have selected hepatitis C virus (HCV), herpes simplex 1 (HSV) and human papilloma virus (HPV) proteins. [107][108][109][110] Certainly, studies using PKR-null mice or MEFs lacking PKR activity have confirmed that this kinase is a key component of the host early defense system, which acts in innate immunity prior to the activation of the IFN system and the acquired immune response.…”
Section: The Regulation Of Pkr By Virusesmentioning
confidence: 99%
“…It has been shown that vIRF3 binds and inhibits p53 transcription factor (25). vIRF3 also inhibits PKR-mediated apoptosis (27) and deregulates IFN-a promoter activity by interacting with cellular IRF3, IRF7, and cyclic AMP-responsive element binding protein-binding protein/ p300 (28,29).…”
Section: Introductionmentioning
confidence: 99%